Mass and nothing sup fat 1H NMR Spectra of the Fe(II) Complex of fat S3N2H2 - Kumar, Manoj; Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
The complex of trithioazyl dihydride, (S3N2H2) with Fe(II), prepared by refluxing the mixture of S3N2H2 and ferrous sulphate in DMF, was analyzed quantitatively and spectrometrically. The chemical data assigned the complex as (S3N2H2)2 FeSO4·7H2O. The spectroscopic data inferred that the complex is hexadentated coordinated complex.